Developing Students’ Digital Awareness and Resilience in Learning Process - Alivi, Justsinta Sindi; Wachidah, Hajar Nurma; Puspitorini, Pipit Sari (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2025)
This paper reported the result of a seminar to develop students’ awareness of the use of technology in their learning process. The seminar also discussed their challenges in the use of technology for learning and how they dealt with it. The seminar highlighted the importance of good digital literacy for students, especially how they should use it to support learning in appropriate ways. The seminar was carried out by having presentation and participants’ questions-answers for discussion. It was indicated in the seminar that students felt technology made their learning easier, especially in terms of the access to resources. Nevertheless, the ease also became challenges as it gave them opportunity to perform cheating and distract them in learning.